Incidence of Injuries in Bhagawanpur, Siraha District, Nepal: a Door-to-Door Survey - Uprety, Samyog; Pyakurel, Prajjwal; Poudel, Masum; Baral, Dharanidhar; Ghimire, Anup (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Rapid industrialization, increasing traffic hazards, and the hectic pace of modern life have exposed people to a greater risk of accidental injuries. We aimed to document the incidence of injuries in the Bhagawanpur Rural Municipality of Siraha District of Nepal and their pattern and cost of treatment.Methods: This cross-sectional study involved 12,935 participants in Bhagawanpur Rural Municipality. A door-to-door survey was conducted from June to August 2018 by face-to-face interview using a preformed semi-structured questionnaire designed for this study. The households were selected by probability proportion to size method from each ward. The variables included the number of injuries, patterns, and costs of treatment.Results: The incidence of injury was 5.3%. The majority (36.2%) belonged to the age group of 16-30 years. The fall injury occurred in 54.2% and superficial bruises affected 70% of injury. Minor injury contributed to about 89.8% and major injury was seen among 10.2% of the study participants. More than half (56%) of the individuals spent less than NPR 1500.00 for the treatment.Conclusion: The incidence of injury was 5.3% among people living in Bhagawanpur Rural Municipality of Siraha District. Most of them were young, and had minor injuries. Treatment costs for most of the injuries were less than NPR 1500.00.